Agrotourism development in Ghana: A study of its prospects and challenges at Adjeikrom Cocoa Tour Facility. - Eshun, Gabriel; Tettey, Christopher (Bulletin of Geography. Socio-economic Series, 2014)
Literature depicts agrotourism as a tool for environmental conservation and rural development. Nonetheless, there is a glaring lacuna in literature concerning agrotourism research from Western Africa. This paper seeks to contribute towards filling this gap in literature. The paper investigates the current situation of agrotourism at Adjeikrom in Ghana, the challenges facing Adjeikrom Cocoa Farm Tour Facility, the opportunities Adjeikrom offers as an agrotourism destination and the role of agrotourism in the socio-economic development of the people of Adjeikrom. Fifty questionnaires were administered to purposively selected residents from Adjeikrom, alongside interviews with the management of the agrotourism facility. The data were analysed using descriptive and inferential statistics. The study revealed that Adjeikrom Cocoa Farm Tour Facility is bereft with challenges such as inadequate skilled personnel, poor state of the Visitor Centre, incoherent marketing of the destination, inadequate Government support and low record of domestic tourists. The study maintains that the Adjeikrom Cocoa Farm Tour Facility has huge prospects for growth if the aforementioned challenges are addressed.